Variants associated with autoimmune Type 1 diabetes in Japanese children: implications for age‐specific effects of cis‐regulatory haplotypes at 17q12‐q21. Issue 12 (15th July 2016) - Ayabe, T.; Fukami, M.; Ogata, T.; Kawamura, T.; Urakami, T.; Kikuchi, N.; Yokota, I.; Ihara, K.; Takemoto, K.; Mukai, T.; Nishii, A.; Kikuchi, T.; et al.
Abstract: Aims: The aim of this study was to clarify the significance of previously reported susceptibility variants in the development of autoimmune Type 1 diabetes in non‐white children. Tested variants included rs2290400, which has been linked to Type 1 diabetes only in one study on white people. Haplotypes at 17q12‐q21 encompassing rs2290400 are known to determine the susceptibility of early‐onset asthma by affecting the expression of flanking genes. Methods: We genotyped 63 variants in 428 Japanese people with childhood‐onset autoimmune Type 1 diabetes and 457 individuals without diabetes. Possible association between variants and age at diabetes onset was examined using age‐specific quantitative trait locus analysis and ordered‐subset regression analysis. Results: Ten variants, including rs2290400 in GSDMB, were more frequent among the people with Type 1 diabetes than those without diabetes. Of these, rs689 in INS and rs231775 in CTLA4 yielded particularly high odds ratios of 5.58 (corrected P value 0.001; 95% CI 2.15–14.47) and 1.64 (corrected P value 5.3 × 10 ‐5 ; 95% CI 1.34–2.01), respectively. Age‐specific effects on diabetes susceptibility were suggested for rs2290400; heterozygosity of the risk alleles was associated with relatively early onset of diabetes, and the allele was linked to the phenotype exclusively in the subgroup of age at onset ≤ 5.0 years. Conclusions: The results indicate that rs2290400 in GSDMB and polymorphisms in INS and CTLA4 are associated with the risk of Type 1 diabetes in Japanese children. Importantly, cis‐regulatory haplotypes at 17q12‐q21 encompassing rs2290400 probably determine the risk of autoimmune Type 1 diabetes predominantly in early childhood. What's new?: Sequence variants including rs2290400 in GSDMB and polymorphisms in INS and CTLA4 are significantly associated with autoimmune Type 1 diabetes in Japanese children. Our results imply that cis‐regulatory haplotypes at 17q12‐q21 encompassing rs2290400 determine the risk of autoimmune Type 1 diabetes predominantly in early childhood.